Peron Media "Koper Dakon" For Learning Mathematics In Basic Schools - Khoirun Nikmah; Sripit Widiastuti; Ida Putri Rarasati (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
Based on the results of observations and interviews, it can be seen that the lack of use of instructional media, the teacher only uses the lecture method. This study aims to determine the feasibility and response of students to the use of platform learning media. The technique used in the research was the Borg and Gall model Rnd method which was limited to the seventh stage, namely product revision. The results of the research showed that the percentage of the assessment of media experts, linguists and material experts were 82.2%, 86.6%, 98.7%, respectively. The average expert score is 89.16%, which means that the average expert score has reached the criteria set in the range of 80.≤x≥100% which is very feasible to use without repair. In the readability test the teacher obtained a percentage value of 81.5% and the student readability test obtained a percentage of 88% with very valid information. While the average percentage of student response assessments is 90%. The conclusion of this study can be stated that the media has received a positive response from students and is suitable for use in mathematics learning in elementary schools.